Times to Diagnosis, Staging, and Treatment of Head and Neck Cancer Before and During COVID-19. Issue 4 (November 2021) - Yao, Peter; Cooley, Victoria; Kuhel, William; Tassler, Andrew; Banuchi, Victoria; Long, Sallie; Savenkov, Oleksandr; Kutler, David Ivan
Objective: The coronavirus disease 2019 (COVID-19) pandemic has reduced the demand for, and supply of, head and neck cancer services. This study compares the times to diagnosis, staging, and treatment of head and neck cancers before and during the COVID-19 pandemic. Study Design: Retrospective cohort study. Setting: Tertiary academic medical center in New York City (NYC). Methods: The times to diagnosis, staging, and treatment of head and neck cancer for patients presenting to the clinics of 4 head and neck oncology surgeons with newly diagnosed head and neck cancers were compared between pre–COVID-19 and COVID-19 periods. Results: Sixty-eight patients in the pre–COVID-19 period and 26 patients in the COVID-19 period presented with newly diagnosed head and neck cancer. Patients in the COVID-19 group had a significantly longer time to diagnosis than the pre–COVID-19 group after adjustment for age and cancer diagnosis ( P = .02; hazard ratio [HR], 0.54; 95% CI, 0.32-0.92). Patients in the pre–COVID-19 and COVID-19 groups had no statistically significant differences in time to staging ( P > .9; HR, 1.01; 95% CI, 0.58-1.74) or time to treatment ( P = .12; HR, 1.55; 95% CI, 0.89-2.72). Conclusion: This study found that time to diagnosis for head and neck cancers was delayed during a COVID-19 period compared to a pre–COVID-19 period. However, there was no evidence of delays in time to staging and time to treatment during the COVID-19 period. Our results prompt further investigations into the factors contributing to diagnostic delays but provide reassurance that despite COVID-19, patients were receiving timely staging and treatment for head and neck cancers.